The Impact of Firm-specific Attributes on the Relevance in Earnings and Cash Flows: Iranian Case - Omid Poorheidari; Mahmood Kohansal (مطالعات تجربی حسابداری مالی, 2005)
The role of accounting information in setting security prices is one of the most fundamental issues in accounting. The purpose of this study is to extend the research on the value relevance of accounting numbers in two important directions. Firstly, we consider the Iran context and analyze if earnings and/or cash flows are relevant to explain stock returns. Secondly, we investigate how firm-specific attributes such as size, leverage and firm life-cycle influence the relative relevance of accounting measures (earnings and cash. flows). Our results support a linear relationship between stock returns and accounting variables. They indicate also that the relevance of earnings is conditional on size, debt level and life cycle of the firm. In contrast, the earning change reveals more information when the firms are small, mature and leverage firms. With regards to cash flows, we find that they do not reveal additional information beyond that contained in earnings.